Analisis Studi Kelayakan Usaha Konveksi Celana Jeans Azqo Collection di Desa Pucung, Kecamatan Tirto, Kabupaten Pekalongan - Faizah, Iis Nur; Abadi, Muhammad Taufiq (CV. Kalimasada Group, 2023)
The marketing concept in the business of Azqo Collection jeans convection with the need itself is a feeling of not having basic satisfaction, desire is the desire for certain satisfaction from the existence of that need, and the next concept is demand is the desire for a product supported by the ability and willingness to buy it. The mix that was carried out at the Azqo Collection jeans convection includes Products sold at the Azqo Collection store include women's jeans, namely: plain jeans culottes, rawis jeans culottes, Gemini pants, and others with excellent product quality, attractive and fashionable at affordable prices. Promotions carried out by the Azqo Collection store are through digital marketing. This study aims to find out how marketing is in the jeans convection business, aspects of the marketing system, and what strategies are faced in facing competition. The type of research used by researchers is descriptive qualitative, namely analyzing, describing, and summarizing the various data collected in the form of interviews or observing the problems studied that occur in the field. The marketing strategy carried out by the Azqo Collection jeans business is to maintain high-quality jeans materials, sell at prices that match the quality, retain customers, and also by looking for more consumers in the market.